ANALYSIS OF FACTORS INFLUENCING THE DECISION OF THE SLICED TAMARIND CRAFTSMEN IN AIR HITAM VILLAGE GEBANG DISTRICT - Dara Meutiasari; Diana Chalil; Iskandarini (CV. Radja Publika, 2023)
Air Hitam Village in Gebang District is one of the areas in Langkat Regency that produces sliced tamarind products. The fluctuating price of sliced tamarind and the price of basic ingredients for tamarind fruit causes a dilemma for craftsmen. This research aims to analyze the factors that influence the decision of sliced tamarind craftsmen to remain as a sliced tamarind craftsmen in Air Hitam Village, Gebang District. This study uses binary logistics analysis. The results showed that the education level and income of the sliced tamarind craftsmen were factors that influenced the decision to remain as sliced tamarind craftsmen in Air Hitam Village, Gebang District.